AI research in forensic sciences (Academic Journal of Internal Affairs, 2018)
The author shows how the emergence of new forms of cybercrime is caused by the artificially created cognitive entities, the narrow knowledge-based AI penetration. With this technology leap, cybercrime is transformed into a qualitative change that means a previously unheard of threat.
Keywords: forensic; AI; cybercrime